75th anniversary to Rustem Gilbrakhmanovich Iblaminov - Osovetskiy, B.; Busygina, N. (Vestnik Permskogo universiteta. Serii͡a︡ Geologii͡a, 2017)
Information about scientific, academic and administrative activity of Dr. Sci., Chair of the Department of Mineralogy and Petrography Rustem Gilbrakhmanovich Iblaminov is presented.